A Single Case Study Of Ayurvedic Management Of Vipadika Kushtha Vis À Vis Palmar Psoriasis - Aggarwal, Vishal; Rani, Tinkle; Gupta, Arun (International Research Journal of Ayurveda & Yoga, 2020)
Palmar Psoriasis is a skin condition which disturbs the beauty of hands substantially affecting the physical as well as psychological life of the person hence affecting the quality of life. In Ayurveda, Palmer Psoriasis shares the similarity with Vipadika Kushtha. Present work is an endeavour to provide a treatment option. Aim: To evaluate the role of Ayurvedic treatment approach in Vipadika Kushtha (Palmar Psoriasis). Materials and Methods: A male patient aged 27 years presented with the signs and symptoms of Vipadika Kushtha, and was treated with both external and internal medications, which included Vaman Therapy (purificatory emesis) and Shamana (palliative treatment). Shodhan was given as Samyak Snehan (proper oleation) followed by Vamana Karma (therapeutic emesis) and Shamana was given by Kaishor Guggulu, Brihat Manjishthadi Kwath, Panchanimba Churna and Jatyadi Taila. Results: At the end of Vamana, Pittantik Vamana was achieved. Patient felt notable reduction in symptoms. Conclusion: This case study showed satisfactory results with the improvement of 80%, could be implemented as a treatment option.